Pengaruh tingkat Likuiditas Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi (Studi Pada Perusahaan Food and Beverage Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023) - Ahada, Shofira Mardiatis; Gitayuda, M. Boy Singgih (Universitas Trunojoyo Madura, 2025)
The purpose of this study is to examine how liquidity affects business value for food and beverage companies listed on the Indonesia Stock Exchange (BEI) between 2019 and 2023, using company size as a moderating variable. The Quick Ratio and Cash Ratio are used to monitor liquidity, which can show how well a firm can meet short-term obligations and affect investors' opinions about its stability and performance. However, it is anticipated that the relationship between liquidity and firm value will either get stronger or weaker depending on the size of the organization, which is determined by its total assets. Price Book Value (PBV), a gauge of market equity, is used to determine a company's worth. The secondary data used in this study was taken from the 2019–2023 annual financial reports of food and beverage companies listed on the Indonesia Stock Exchange. To evaluate the link between these factors, a quantitative approach with moderation was employed as the analytical method in this study. The study's findings indicate that while the cash ratio has a negative impact on company value, the current ratio and quick ratio have a positive impact.